Comparative Study of The National Agrarian Legal System With Countries in Asean (Study of Law Number 5 of 1960 and Government Regulation Number 18 of 2021) - Aulia Husein, Ridho; Arifin Hoesin, Zainal (Sahabat Publikasi, 2025)
The agrarian law system plays an important role in the development and management of a country's land resources. In Indonesia, this system is regulated by Law Number 5 of 1960 (UUPA) and Government Regulation Number 18 of 2021, which aims to create social justice and sustainable land management. However, the implementation of the agrarian law system in Indonesia still faces various challenges and legal uncertainties. This research aims to compare the national agrarian law system with ASEAN countries to identify weaknesses and take best practices to strengthen Indonesia's agrarian system. This research uses a normative legal method with a comparative approach, relying on primary and secondary data analyzed descriptively qualitatively. The results show that ASEAN countries, such as the Philippines, Malaysia and Singapore, have different approaches to land management. The Philippines applies the Regalian Doctrine, Malaysia delegates land management to the states, while Singapore optimizes urban planning through state ownership of the majority of land. The strengths of Indonesia's agrarian law system lie in the application of social justice principles and the recognition of indigenous peoples' rights, but Indonesia still faces challenges such as legal dualism between customary and state law, bureaucratic red tape, corrupt practices, and lack of transparency. Thus, while Indonesia has the potential to create a just and sustainable agrarian system, lessons learned from ASEAN countries can help improve existing weaknesses and strengthen national agrarian governance.